NILAI-NILAI KEARIFAN BUDAYA LOKAL TEMBANG SUNDA NYOREANG NYAWANG DAN LAJUNING LAKU PATANJALA SEBAGAI UPAYA KONSERVASI LINGKUNGAN DI BOGOR - Swastikanthi, Agatha Trisari; Septriani, Hilda (Universitas Pakuan, 2024)
Local cultural wisdom is based on locality. One of the forms of locality is the tembang. Sundanese songs that are part of oral literature today are not as much as they used to be, but there is still a group of people who still maintain the existence of these songs. One of them is as a means of invitation to build awareness in protecting nature and the environment. The data of this research is Sunda Nyoreang Nyawang and Lajuning Laku Patanjala. This study aims to identify the structure of the Sundanese Nyoreang Nyawang and Lajuning Laku Patanjala songs and identify the values of local cultural wisdom manifested in the Sundanese Nyoreang Nyawang and Lajuning Laku Patanjala songs. This research uses a qualitative method. The theory used is that of Charles Sanders Pierce's semiotics. The data analysis technique begins by recording words related to local wisdom, to further reveal the conceptual meaning of each word that is used as data in the research. The results of this study show that the two songs represent the values of local cultural wisdom contained in the lyrics of the songs and are evidence of the footsteps of their creators related to concern for the environment and concern for others to continue to be aware of protecting the environment together.Keywords: Konservasi; value of local wisdom; tembang